2015
DOI: 10.1002/cncr.29475
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of acquired copy‐neutral loss of heterozygosity in acute myeloid leukemia

Abstract: BACKGROUND Chromosomal abnormalities are important in the diagnosis and prognosis of patients with acute myeloid leukemia (AML). Genomic microarray techniques detect recurrent copy‐neutral loss of heterozygosity (cnLOH) in addition to copy number aberrations. However, the clinical utility has not been fully established. Therefore, in the current study, the authors examined the prognostic impact of acquired cnLOH in patients with AML, including complete remission (CR) rate, duration of CR, and overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…25,[30][31][32][33][34][35][36][37] Gronseth and colleagues have already noted that the WHO classification does not currently include the prognostic significance of microarray findings. 38 Our results are consistent with previously published data regarding the prognostic significance of cryptic abnormalities detected using molecular cytogenomic techniques, which can significantly affect the OS of MDS patients. 30,31,38 Ongoing studies with larger cohorts of patients may provide more information about the prognostic effects of the cryptic CNA and CN-LOH detected using cytogenomic techniques.…”
Section: Microarray Analysissupporting
confidence: 92%
“…25,[30][31][32][33][34][35][36][37] Gronseth and colleagues have already noted that the WHO classification does not currently include the prognostic significance of microarray findings. 38 Our results are consistent with previously published data regarding the prognostic significance of cryptic abnormalities detected using molecular cytogenomic techniques, which can significantly affect the OS of MDS patients. 30,31,38 Ongoing studies with larger cohorts of patients may provide more information about the prognostic effects of the cryptic CNA and CN-LOH detected using cytogenomic techniques.…”
Section: Microarray Analysissupporting
confidence: 92%
“…Patient 1 in the present study showed a karyotype with isolated t(7;21); however, GMA identified cnLOH of 11p in 25% of the sample, which was consistent with the tumor burden detected by flow cytometry. 11p is reported as one of the most common sites of acquired cnLOH in AML patients, presenting with impacts on the overall survival rate and recurrence risk . As coincident findings in AML with t(7;21), del(5q) and cnLOH 11p may be linked to the variability in clinical and pathological manifestations.…”
Section: Discussionmentioning
confidence: 89%
“…11p is reported as one of the most common sites of acquired cnLOH in AML patients, presenting with impacts on the overall survival rate and recurrence risk. 24 As coincident findings in AML with t (7;21), del(5q) and cnLOH 11p may be linked to the variability in clinical and pathological manifestations. Alternatively, they may act as second hit mutations to the initiating event t(7;21) in leukemia.…”
Section: Discussionmentioning
confidence: 90%
“…91 However, this heterozygous status is unstable, and loss of heterozygosity (LOH) frequently follows in malignant progression and holds prognostic impact. 92,93 LOH is indicative of pressure to inactivate the remaining TP53 allele and is found in t-AML, AML postmyeloproliferative Philadelphia1 (Ph1)-negative neoplasms, and LFSrelated AML. 6,18,94 Missense mutations of TP53 frequently yield LOF phenotypes, abrogating sequence-specific DNA-binding activity toward TP53 responsive elements.…”
Section: Aml-related Tp53 Mutationsmentioning
confidence: 99%